Design and Analysis of Connecting Tie Rod Assembly for Automotive Application - Aravindaraj E.; Natrayan L.; Santhosh M. S.; Kumar M.S. (Журнал інженерних наук)
The tie rod end is one of the most elementary parts of a steering mechanism, which has direct and crucial importance in terms of driving safety. The tie rod end is used to ensure that the wheels are aligned. It provides the adjustment for the wheel to align and keeps the tires free from wearing out on the inner as well as outer edges. Hence the functioning of the tie rod is crucial for steering as well as suspension performance of the vehicle. Today’s world is competitive. Market demands the advanced technology at a lower price. This reflects in making the technology cheaper. Hence every industry determined for the cost-effective product at a lower price and within minimum period for ‘time to market. This puts a lot of pressure on engineers to consistently strive to design the more effective products at the lower price. The work is focused on the functioning of the tie rod. Generally, tractor connecting tie rod gets failed due to the overload applications. This paper focuses on modifying the old tie rod design and material. Finally, analysis the load causes of existing and modified design using ANSYS software. This modelling approach, the stress variations and deformation characteristics of each component are investigated for high operational loading conditions.